Effect of oxygen on the electrical characteristics of field effect transistors formed from electrochemically deposited films of poly(3-methylthiophene) - Taylor, D. M. (2015)
Field effect devices have been formed in which the active layer is a thin film of poly(3-methylthiophene) grown electrochemically onto preformed source and drain electrodes. Although a field effect is present after electrochemical undoping, stable device characteristics with a high modulation ratio are obtained only after vacuum annealing at an elevated temperature, and only then if the devices are held in vacuo. The polymer is shown to be p type and the devices operate in accumulation only. The hole mobility in devices thermally annealed under vacuum is around 10 -3 cm 2 V -1 s -1. On exposure to ambient laboratory air, the device conductance increases by several orders of magnitude. This increase may be reversed by subjecting the device to a further high-temperature anneal under vacuum. Subsidiary experiments show that these effects are caused by the reversible doping of the polymer by gaseous oxygen.